Toward equitable urban water supply and sanitation in Dar es Salaam: The dialectic relationship between policy-driven and everyday practices. (October 2022) - Hofmann, Pascale
Abstract: Many cities in the Global South continue to struggle with providing services with increasing inequalities in the distribution of and access to safe drinking water. For lower-income inhabitants, access changes over time and is shaped by the interplay between practices driven by policy and the range of diverse everyday practices in low-income areas. Existing practices are entangled with the evolution of the natural and built environment in which human-nature interactions are continuously negotiated in situ and over time through different infrastructure and service configurations that can alter water flows, social relations, and practices. Focusing on the case of Dar es Salaam, this paper examines policy-driven practices by the utility (and other key players in formal service provision) and their interaction with everyday practices to spell out implications for urban (in)equality. The paper draws on research grounded in a normative perspective based on principles of environmental justice, emphasising agency-structure debates and intersectionality scholarship. The approach enables a critical multi-scalar analysis that reveals differential abilities and vulnerabilities among poor women and men toward enabling and restraining structural processes and conditions, whereby time, space and socio-environmental relations intersect with and influence infrastructural and service configurations and vice versa. Findings confirm a dialectic relationship between policy-driven and everyday practices with multiple examples where practices reproduce, reinforce, or distort existing inequalities. However, the findings further show instances of more transformative practices that challenge unjust processes and outcomes toward more equitable service provision. Highlights: Service provision inequalities in low-income settlements are shaped by a dialectic interplay between policy-driven and everyday practices. An examination of this interplay offers insights into the potential for more just, sustainable, and resilient systems. Bottom-up approaches can bridge policy-driven and everyday practices toward inclusive service provision arrangements. Transformative change starts with perceptions about the permanency and malleability of existing practices.